Influence of basic complex two-year therapy on indicators of late remodeling of the left ventricle and prophylaxis of the occurrence of cardiovascular events in patients after unstable angina combined with arterial hypertension - O. V. Denesiuk; V. I. Denesiuk (Patologìâ)
The purpose of the study was to determine the effect of basic complex biennial treatment on the parameters of late remodeling of the left ventricle (LV) and cardiovascular events in patients after unstable angina (UA) in combination with arterial hypertension (AH).